Knowledge And Attitude of Substance Abuse Among Medical and Pharmacy Students at The University of Al-Qadisiyah - Kareem, Rania I.; Jallab, Hassan R. (Medical Science Journal for Advance Research, 2026)
Background: Substance abuse continues to be an increasing public health issue globally, especially among adolescents and young adults, including undergraduate students. Medical and pharmacy students’ knowledge and attitudes toward substance abuse are crucial given their future roles in prevention, early detection, and intervention. Objective: To evaluate the level of knowledge and attitudes toward substance abuse among undergraduate medical and pharmacy students. Methods:This cross-sectional study was carried out on a convenience sample of 400 undergraduate Medical and Pharmacy students at the University of Al-Qadissiyah, Diwaniyah City, Iraq, from all academic years, between March 1 and August 31, 2025. Data was collected using a structured self-administered questionnaire that included three sections, covering demographic, knowledge, and attitude toward substance abuse. Statistical analyses were conducted using SPSS (v. 28). Results:Survey analysis revealed that of 400 health-care students (mean age 21.26 ± 2.10 years; 53.5% female; 87.8% urban; 93.0% single). Investigating general knowledge of the enrolled students showed that 112(28%) of respondents had poor knowledge score, 161(40.2%) had satisfactory knowledge score and 127(31.8%) had good knowledge score, where awareness of classic addictive agents such as nicotine (79.5%), alcohol (78.5%), and cocaine (78.0%) was high, whereas knowledge of relatively newer substances like pregabalin (51.3%) and cough syrup (58.5%) was lower. Attitudinally, most students agreed that addiction is a medical disease (54.8%), medical treatment is effective (70.5%), and increasing health education can help prevent addiction (69.8%). The studying of student attitude regarding substance abuse shown that: only 50(12.5%) had good attitude score, 134(33.5%) had satisfactory attitude score and 216(54%) had poor attitude score. Conclusion:Students responses showed acceptable knowledge levels with low attitude score. The study highlights a gap in attitude toward substance abuse among future healthcare professionals.